PURPOSE AND TASKS OF PSYCHOLOGICAL SERVICE IN EDUCATIONAL INSTITUTIONS - Xaydarova Zuhra Choriyevna (Journals Park Publishing, 2024)
This scientific study provides general information about the role and importance of psychological services in the educational system. It explores the various functions and benefits of integrating psychological support in educational settings to positively impact students' academic, social, and emotional well-being. It also examines challenges and potential solutions to implementing effective psychological services in schools. The results highlight the importance of collaboration between teachers, psychologists and other stakeholders to ensure comprehensive and inclusive support for students.
Keywords: psychological services, educational system, academic support, social-emotional well-being, cooperation, comprehensive support.